2021
DOI: 10.3390/jcm10184139
|View full text |Cite
|
Sign up to set email alerts
|

Severe Traumatic Injury Induces Phenotypic and Functional Changes of Neutrophils and Monocytes

Abstract: Background: Severe traumatic injury has been associated with high susceptibility for the development of secondary complications caused by dysbalanced immune response. As the first line of the cellular immune response, neutrophils and monocytes recruited to the site of tissue damage and/or infection, are divided into three different subsets according to their CD16/CD62L and CD16/CD14 expression, respectively. Their differential functions have not yet been clearly understood. Thus, we evaluated the phenotypic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
2
12
1
Order By: Relevance
“…In contrast with Janicova's study [73], we did not detect changes in either the intermediate CD14 + CD16 + or classical CD14 hi CD16-monocyte populations. The different type of sample (fresh whole blood vs thawed PBMC), and the different score of injury (severe TBI vs severe, moderate, and mild TBI), could account for the differences observed between the study performed by Janicova and colleagues [73] and our investigation. Also, the different sample timing (within the rst 12 h post-injury vs a media of 21h) was shown to be a fundamental aspect when considering immune trauma-induced changes [18].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with Janicova's study [73], we did not detect changes in either the intermediate CD14 + CD16 + or classical CD14 hi CD16-monocyte populations. The different type of sample (fresh whole blood vs thawed PBMC), and the different score of injury (severe TBI vs severe, moderate, and mild TBI), could account for the differences observed between the study performed by Janicova and colleagues [73] and our investigation. Also, the different sample timing (within the rst 12 h post-injury vs a media of 21h) was shown to be a fundamental aspect when considering immune trauma-induced changes [18].…”
Section: Discussioncontrasting
confidence: 99%
“…CD45 + cells were further differentiated into neutrophilic and eosinophilic granulocytes (SSC hi ) and PBMC (SSC lo ). Peripheral blood neutrophils were homogeneous and express FcγRIII (CD16) and L-selectin (CD62L) within a narrow range, typically characterized as CD16 bright CD62L bright (mature), CD16 dim CD62L bright (immature), CD16 dim CD62L dim (apoptotic) neutrophils ( 22 ). L-selectin(CD62L) can account for impaired rolling and migration ability of leukocytes ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although monocyte or macrophage subtypes could not be investigated, we found that total wound macrophage numbers were increased and that the production of inflammatory mediators by macrophages was enhanced. Activity of neutrophils is altered after severe trauma in animals (Baskaran et al 2000;Janicova et al 2021;Leliefeld et al 2016;Mortaz et al 2018), but it remains unclear whether trauma in general enhances or weakens neutrophil activity (Figure 5). Presumably, the emergency-release of neutrophils into the circulation is responsible for reduced chemotactic activity due to inflexibility of the banded nucleus of immature neutrophils (Drifte et al 2013), while rapid activation can lead to impaired antibacterial activity (Leliefeld et al 2016).…”
Section: Discussionmentioning
confidence: 99%